Pengaruh Relaksasi Otot Progresif dan Cognitif Behavior Therapy Terhadap Kecemasan Pada Siswa SMP di Kecamatan Cugenang Kabupaten Cianjur - Ricky Alwi Hermawan; Ni Made Dian; Fauziah Rudhiati (Universitas Pahlawan Tuanku Tambusai, 2025)
Post-Traumatic Stress Disorder (PTSD) is a response to extreme trauma in areas prone to earthquakes. This study aims to identify the effects of Progressive Muscle Relaxation (ROP) and Cognitive Behavioral Therapy (CBT) on anxiety among junior high school students with PTSD in Cugenang District, Cianjur Regency. This design of this research was Quasi-Experimental study using a pre and post-test with control design. The sample of this study consists of 24 students from SMP 2 and SMP 3 Cugenang, Cianjur Regency, who are experiencing post-disaster anxiety, selected through random sampling. The research instrument used is the Hamilton Anxiety Rating Scale (HARS). The data analysis employed is the Paired Sample Test. The results of the study demonstrate the effect of Progressive Muscle Relaxation and Cognitive Behavioral Therapy on anxiety before and after the intervention, with a significant difference between the control and intervention groups of junior high school students with PTSD in Cugenang District, Cianjur Regency, with a significance value of 0.000 (p < 0.05). Based on the results, it is recommended that ROP and CBT be implemented for children to reduce PTSD-related anxiety after a disaster.